2017
DOI: 10.3390/en10030276
|View full text |Cite
|
Sign up to set email alerts
|

Using a Hybrid Cost-FMEA Analysis for Wind Turbine Reliability Analysis

Abstract: Abstract:Failure mode and effects analysis (FMEA) has been proven to be an effective methodology to improve system design reliability. However, the standard approach reveals some weaknesses when applied to wind turbine systems. The conventional criticality assessment method has been criticized as having many limitations such as the weighting of severity and detection factors. In this paper, we aim to overcome these drawbacks and develop a hybrid cost-FMEA by integrating cost factors to assess the criticality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 34 publications
(50 reference statements)
2
48
1
2
Order By: Relevance
“…The average matrix D was calculated based on pairwise comparisons according to five-levelled scales (0 = no effect, 1 = low effect, 2 = media effect, 3 = high effect, 4 = very high effect). Then, the total influence matrix T was derived from Equations (8)- (10). In sum, the total relation matrix for the main clusters is shown in Table 5.…”
Section: Interrelationships Among Clusters and Fmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average matrix D was calculated based on pairwise comparisons according to five-levelled scales (0 = no effect, 1 = low effect, 2 = media effect, 3 = high effect, 4 = very high effect). Then, the total influence matrix T was derived from Equations (8)- (10). In sum, the total relation matrix for the main clusters is shown in Table 5.…”
Section: Interrelationships Among Clusters and Fmsmentioning
confidence: 99%
“…Also, the comparisons of the proposed framework with previous studies demonstrated the multidisciplinary applications of the present framework. Energies 2019, 12, 649 2 of 22Studies have shown that FMEA has a wide area of application that ranges from wind turbine reliability, healthcare, automotive, nuclear, and manufacturing [9][10][11][12][13]. Moreover, in the electrical distribution field, FMEA has been used in the determination of critical equipment and is mostly combined with a reliability centered maintenance (RCM) to improve the maintenance reliability [14].The work of Matteson [15] shows the identification process for FMs and their consequences with the classification of the severity and occurrence.…”
mentioning
confidence: 99%
“…In the Definition 6, we replace p i and p j with p w i i and p w i j , respectively, according to Equation (6). Similar to the proof of Theorem 1, we obtained IVPFWGBM x,y (p 1 , p 2 , · · · , pn) = 1…”
Section: Appendixmentioning
confidence: 85%
“…As a formal system analysis approach, the technique of FMEA was originally proposed in the 1960s, and was intended to satisfy the aerospace industry's apparent safety and reliability requirements [4]. Since then, the FMEA method has been successfully used in various industries as a simple and powerful tool to enhance the safety and reliability of products, systems, and processes in industry, such as the aerospace [5], energy [6], heath care and hospital [7], and manufacturing industries [8].…”
Section: Introductionmentioning
confidence: 99%
“…Wind farm reliability is a subject of interest to industry and academia [1][2][3][4]. The availability of wind as a resource alongside the reliability of wind turbine generators may significantly affect power system reliability [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%